Besiru sebagai Konsep Desain Poster Pameran Art Mandalika - Gunalan, Sasih; Satria, Christofer; Haryono, Haryono (Jurnal SASAK : Desain Visual dan Komunikasi, 2023)
ABSTRACTExhibitions can be one of the artistic patterns in presenting works, which are personal or individualistic. These artistic patterns can continue to be carried out by artists in strengthening their existence in the midst of the existing art field. The Mandalika art exhibition carries the theme Besiru as a representation of locality in covering various locality approaches that exist in the tribes of West Nusa Tenggara. Besiru is a social pattern that many people are starting to forget in the midst of modernization.The type of approach used is qualitative research with a naturalistic approach. Qualitative research or also known as naturalistic research. Data analysis techniques are carried out through the activities of collecting data, reducing data, classifying data, analyzing and drawing conclusions. The theoretical study used in this paper is Stuart Hall's representation theory.The conclusion of this study is that all components of design publication, work concept and exhibition management have a common thread with the exhibition theme, namely Besiru. The theme is present as a shared representation of a traditional activity that has begun to be forgotten. The relevance of the Besiru tradition as part of the Mandalika art can be found in the design of the publication and several other things. The illustration of the poster design for the Mandalika art exhibition, taken from several images done by the artists in collaborative installations and individual works. Apart from the exhibition design concept, the philosophical theme of Besiru is also implemented through a curatorial design written by the curator. Besiru's concept and philosophy also became the framework for the artists in creating three collaborative works that they worked on together.Keyword : Besiru, Design, Poster, Fine Art Exhibition